Fundamentals and the Equilibrium of Real Exchange Rate of an Emerging Economy: Estimating the Exchange Rate Misalignment in Malaysia - Jauhari Dahalan; Mohammed Umar; Hussin Abdullah (International Journal of Economics and Financial Issues, 2016)
To evaluate the existence of possible over and under valuation of exchange rate for Malaysia, the study examines the nature of misalignment in the equilibrium real exchange rate and its systemic and structural changes in the fundamentals. We account for structural breaks in the data generating process to determine the appropriate order of integration. Based on the suggestion of the weak exogeneity and unit vector analysis, the study estimates the equilibrium and sustainable equilibrium real exchange rate based on the behavioural equilibrium exchange rate (BEER) model using multivariate Johansen cointegration and dynamic ordinary least squares (DOLS) techniques. The result reveals that variation in the sustainable equilibrium real exchange rate (SREER) is collectively accounted by the real capital formation, government consumption expenditure, capital flows and degree of openness. Furthermore, the study identifies changes in the final consumption expenditure as the major factor that leads to persistent variation in the real exchange rate. Nevertheless, the SREER consistently appreciates slightly throughout the sample period with little forms of neutralized depreciation. The consistency in the SREER appreciation is accounted for by the increase in real capital formation. Moreover, the finding on misalignment shows three episodes; the relative sustainable equilibrium with slight evidence of fluctuation; a bit undervaluation with trivial adjustment and the episodes of overvaluation. The policy implication of the study is that, policymakers should focus on fiscal policies that work towards greater import substitution strategies; inter-temporal substitution effect of close substitute of non-tradable commodities and monetary policies that reduce capital outflows.